Direct Transformation of N, N′‐Methylene Bisacrylamide Self‐Assembled Fibers Into Polymer Microtubes via RAFT Polymerization. Issue 2 (9th November 2012) - Li, Qi; Tang, Liming; Xia, Yu; Li, Botian
Abstract A novel fabrication method of polymer tubes with simple operation process and high yield is presented. N, N′‐methylene bisacrylamide (MBA) polymer microtubes are fabricated via reversible addition–fragmentation chain transfer (RAFT) polymerization using MBA self‐assembled fibers as both the template and monomer source. The resulting products are characterized by SEM, TEM, FTIR, and element analysis. The mechanical properties of the gel‐like product and the MBA organogel are measured by rheometer. The morphology of the polymer tubes obtained via RAFT polymerization is compared with the sample obtained via conventional radical polymerization. Based on the current investigations, the fabrication mechanism of this method is initially proposed.